Manometer Design For Measuring Head Losses In Piping Test: Rancang Bangun Manometer Untuk Alat Ukur Head Losses Pada Uji Perpipaan - Fernando, Ekki; Fahruddin, A'rasy (Indonesian Journal of Innovation Studies, 2021)
For the manometer that will be used in this study, using a U column type manometer filled with a fluid for measuring pressure, this manometer was designed using a simple tool at the time of manufacture. This manometer will be tested for its level of accuracy in the Head Losses test on the piping system. That is by using 3 types of fluids, namely resin, glycerol, and mercury where the pressure is generated from the flow of water in a straight pipe and an Elbow where this Manometer is placed in a straight pipe and also in the Elbow so here using 2 Manometers for testing. Then the test is carried out according to the specified variables, in order to obtain research data. After that determine the results of the pressure measurement of the 3 types of fluids used. The pressure measurement uses water discharge measuring 20, 15, and 10L/min. Then determine each result from each fluid where each fluid is experimented 3 times to determine the average value. If you have obtained the average value of each height difference (∆h) in each fluid, then determine the pressure value (Pa). The results of the Head Losses test on the piping test show that the resin value is close to the mercury value while the glycerol value is quite far. This shows that the density value of each fluid has an influence on the pressure value of each fluid. Keywords – Manometer; Pipe; Pressure; Head losses; resins; Glycerol; Mercury